ANALYZING THE TRUMPISM IN THE US FOREIGN POLICY TOWARDS CHINA: THE CONTINUITY OF COLD WAR - Dr. Nasreen Akhtar; Dr. Inamullah Jan (Policy Research Journal, 2025)
This article examines Trump’s foreign policy towards China and its impacts on the trade relations between the United States (US) and China. Trump’s China-specific policy had great impacts on diplomatic and political relations. China’s global strategic policy was viewed as a global threat that immensely alarmed the Trump administration, which developed the notion of ‘Trumpism.’ The growing influence of China has raised concern for the US. Chinese military and economic engagements in Asia and beyond are viewed as a direct threat to US hegemony. The article delves into the strategic competition between the US and China as the New World War in the immensely politically polarized world and analyses the factors of the rivalry between the US and China. The main objective of this article is to interpret the US-China-centric policy that led to the New Cold War between the two major powers. We also explain the measures that amplified potential threats between the US and China.